Morbidity associated with Schistosoma mansoni infection in north-eastern Democratic Republic of the Congo - Nigo, Maurice M.; Odermatt, Peter; Nigo, David Wully; Salieb-Beugelaar, Georgette B.; Battegay, Manuel; Hunziker, Patrick R. (PLOS Neglected Tropical Diseases, 2021)
Background Reducing morbidity is the main target of schistosomiasis control efforts, yet only rarely do control programmes assess morbidity linked to Schistosoma sp. infection. In the Democratic Republic of Congo (DRC), and particularly in north-eastern Ituri Province, little is known about morbidity associated with Schistosoma mansoni infection. For this reason, we aimed to assess intestinal and hepatosplenic morbidity associated with S. mansoni infection in Ituri Province. Methods/Principal findings In 2017, we conducted a cross-sectional study in 13 villages in Ituri Province, DRC. S. mansoni infection was assessed with a Kato-Katz stool test (2 smears) and a point-of-care circulating cathodic antigen (POC-CCA) urine test. A questionnaire was used to obtain demographic data and information about experienced intestinal morbidity. Each participant underwent an abdominal ultrasonography examination to diagnose hepatosplenic morbidity. Of the 586 study participants, 76.6% tested positive for S. mansoni. Intestinal morbidity reported in the two preceding weeks was very frequent, and included abdominal pain (52.7%), diarrhoea (23.4%) and blood in the stool (21.5%). Hepatosplenic morbidity consisted of abnormal liver parenchyma patterns (42.8%), hepatomegaly (26.5%) and splenomegaly (25.3%). Liver pathology (adjusted odds ratio [aOR] 1.20, 95% confidence interval [CI] 1.06–1.37, p = 0.005) was positively and significantly associated with S. mansoni infection. Hepatomegaly (aOR 1.52, 95% CI 0.99–2.32, p = 0.053) and splenomegaly (aOR 1.12, 95% CI 0.73–1.72, p = 0.619) were positively but not significantly associated with S. mansoni infection at the individual level. At the village level, S. mansoni prevalence was positively associated with the prevalence of hepatomegaly and splenomegaly. High-intensity S. mansoni infections were associated with diarrhoea, blood in the stool, hepatomegaly, splenomegaly, and liver parenchyma (C, D, E and F pathology patterns). Four study participants were diagnosed with ascites and five reported hematemesis. Conclusions/Significance Our study documents a high burden of intestinal and hepatosplenic morbidity associated with S. mansoni infection status in Ituri Province. The findings call for targeted interventions to address both S. mansoni infection and related morbidity.